Microbiome interactions with different risk factors in development of myocardial infarction - Bijla, Manisha; Saini, Sunil Kumar; Pathak, Ajai Kumar; Bharadwaj, Kamal Prakash; Sukhavasi, Katyayani; Patil, Ayurshi; Saini, Diksha; Yadav, Rakesh; Singh, Shalini; Leeuwenburgh, Christiaan; Kumar, Pramod (Experimental gerontology, 2024)
Among all non-communicable diseases, Cardiovascular Diseases (CVDs) stand as the leading global cause of mortality. Within this spectrum, Myocardial Infarction (MI) strikingly accounts for over 15 % of all deaths. The intricate web of risk factors for MI, comprising family history, tobacco use, oral health, hypertension, nutritional pattern, and microbial infections, is firmly influenced by the human gut and oral microbiota, their diversity, richness, and dysbiosis, along with their respective metabolites. Host genetic factors, especially allelic variations in signaling and inflammatory markers, greatly affect the progression or severity of the disease. Despite the established significance of the human microbiome-nutrient-metabolite interplay in associations with CVDs, the unexplored terrain of the gut-heart-oral axis has risen as a critical knowledge gap. Moreover, the pivotal role of the microbiome and the complex interplay with host genetics, compounded by age-related changes, emerges as an area of vital importance in the development of MI. In addition, a distinctive disease susceptibility and severity influenced by gender-based or ancestral differences, adds a crucial insights to the association with increased mortality. Here, we aimed to provide an overview on interactions of microbiome (oral and gut) with major risk factors (tobacco use, alcohol consumption, diet, hypertension host genetics, gender, and aging) in the development of MI and therapeutic regulation. [Display omitted] •Interactions of Microbiome in humans is associated with development of Myocardial Infarction (MI).•Short Chain Fatty Acids (SCFA) play an essential role in the maintenance of intestinal homeostasis.•Elevated levels of TMAO associated with development of MI.